2005
DOI: 10.1073/pnas.0501263102
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent nestin-positive, keratin-negative hair-follicle bulge stem cells can form neurons

Abstract: We have recently shown that the expression of nestin, the neural stem cell marker protein, is expressed in bulge-area stem cells of the hair follicle. We used transgenic mice with GFP expression driven by the nestin regulatory element [nestin-driven GFP (ND-GFP)]. The ND-GFP stem cells give rise to the outer-root sheath of the hair follicle as well as an ND-GFP interfollicular vascular network. In this study, we demonstrate that ND-GFP stem cells isolated from the hair-follicle bulge area that are negative for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
358
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 394 publications
(376 citation statements)
references
References 16 publications
14
358
2
2
Order By: Relevance
“…However, this is a difficult problem, and although the task is urgent, it will be some time before it is possible to guarantee sufficient safety to enable stem cell use in clinical settings. Prior to any clinical trial of human CNS disorders using iPS cells, it will be essential to pre-evaluate each iPS cell clone carefully to be able to guarantee a safety level equal to other types of cells, such as hair follicle stem cells [45][46][47][48][49][50][51], multipotent skin-derived precursor cells [52,53], fetusderived neural stem/progenitor cells [54], and neural crest stem cells [55]. Moreover, experiments on primates will be essential, as preclinical studies before transplantation can be tried in SCI patients [56].…”
Section: Future Prospects and Tasksmentioning
confidence: 99%
“…However, this is a difficult problem, and although the task is urgent, it will be some time before it is possible to guarantee sufficient safety to enable stem cell use in clinical settings. Prior to any clinical trial of human CNS disorders using iPS cells, it will be essential to pre-evaluate each iPS cell clone carefully to be able to guarantee a safety level equal to other types of cells, such as hair follicle stem cells [45][46][47][48][49][50][51], multipotent skin-derived precursor cells [52,53], fetusderived neural stem/progenitor cells [54], and neural crest stem cells [55]. Moreover, experiments on primates will be essential, as preclinical studies before transplantation can be tried in SCI patients [56].…”
Section: Future Prospects and Tasksmentioning
confidence: 99%
“…Apparently, further studies are necessary to clarify the in vivo mechanisms restricting the multipotential capability of Sox10þ NC cells. Also, in this context, multipotential stem cells established from dissociated skin (Fernandes et al, 2004;Amoh et al, 2005) could possibly be generated from a differentiated subpopulation of NC cells such as Sox10þ/Kitþ melanoblast precursors.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…4 Our laboratory discovered hair-follicle-associated pluripotent (HAP) stem cells, located in the bulge area, 5 HAP stem cells from mouse expressed nestin and could differentiate to neurons, glia, keratinocytes, smooth-muscle cells, and melanocytes in vitro. 6,7 HAP stem cells from mouse could effect nerve repair 8,9 and spinal cord regeneration 10 in mouse models. We then demonstrated that mouse HAP stem cells differentiate to beating cardiac-muscle cells.…”
Section: Introductionmentioning
confidence: 99%